Optimal battery based electrical reconfiguration technique for partial shaded PV system - P, Aravind; D, Prince Winston; S, Sugumar; M, Pravin (Applied energy, 2024)
In tackling the challenges associated with partial shading scenarios in solar photovoltaic (PV) arrays, this study introduces a groundbreaking approach to dynamic reconfiguration: the Optimal Battery-based Electrical Reconfiguration (OBER). Unlike conventional methods like the Couple Matching (CM) algorithm, OBER directly addresses the impact of shading on PV performance. By strategically connecting the strongest and weakest rows of both genders, OBER aims to overcome performance disparities induced by shading. A key innovation in OBER is the use of an external battery to augment energy in the weakest row, resulting in a substantial increase in array current and overall power output. Using MATLAB simulation, this study compares OBER with traditional methods like the New Column Index Method (NCIM), Square Dynamic Reconfiguration (SDR), and CM across ten partial shading scenarios. The proposed OBER outperforms TCT, NCIM, SDR, and CM in Pmax generation by 8.3% to 46.5%. OBER proves to be a transformative approach, promising efficiency enhancements and positioning itself as a key advancement in dynamically responsive solar PV systems. The experimental validation of OBER's performance reinforces its potential to significantly increase power output, providing a promising solution for optimizing solar PV arrays under challenging shading conditions. •OBER introduces a solution for PV shading challenges.•It strategically connects rows without gender alignment.•The breakthrough involves an external battery boosting the array power.•OBER outperforms traditional methods by 8.3% to 46.5% in MATLAB simulations.•Effectiveness in diverse shading patterns showcases adaptability.